Engineering Research - Microscopic Study of California Oil-field Emulsions - Kenneth S. Ritchie (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1931)
The natural emulsion samples used in this study were shipped directly from twelve California oil fields, through the courtesy of the superintendents of the main producing companies in those fields. Representative parts of each sample were chosen for the slides. Preparation of the slides was generally made in less than two minutes, including time of exposure; in a few cases, about five minutes was required. The short time was intended to minirmize the changes in conditions. Whenever comparison was of value, standard conditions were established. Spreading by gravity was adopted instead of smearing. Cover glasses were not allowed to rest on the films. General Characteristics of Emulsions The main purpose of the general views (Figs. 1-16) is to illustrate the general characteristics of the dispersed droplets together with any other constituent or impurity that may be found in each emulsion. The magnification is given so that dimensions could be measured from the plates. The slides used for these views had spherical recesses; they gave the best light. Where crystals were intended to be shown in the picture a filter (green was the best') was usually used. Emulsions that showed a tendency to move by concentrated light were pictured without a condenser.